Seed Certification Standards for Quality Planting Material Production of Cassava, Sweet Potato, Lesser Yam and Taro - Muthuraj, R; George, James; Ravi, V (JOURNAL OF ROOT CROPS, 2016)
Tropical tuber crops are propagated through vegetative method of propagation. This method of propagation includes micropropagation which facilitates faster multiplication of true to type clones. High yielding clones can be propagated faster using vegetative method of propagation without going for generation to achieve stabilization. However, due to the presence of large number of viruses and virus like organisms, there are all possibilities for transmission of diseases through clonal propagation, many of will be lethal. Furthermore, tuber crops have long duration and any mistake done in the choice of cultivar, quality of planting material and seed may invite more risks to the farmers. Quality seed/planting material therefore is one of the most important determinants of tuber crop production, which influences the output apart from other inputs like fertilizer, water management, pesticide etc. The efforts taken for several years may become futile, if true to type, healthy and disease- free planting material is not used. Therefore, quality of planting material of tuber crops with minimum seed certification standards assumes greater significance in the development and production of tuber crops.